Obesity in Nigeria children and adolescents-waist circumference a more sensitive indicator - Johnson, Olubusola E.; Mbada, Chidozie E.; Alao, Damilola Y.; Okonji, Adaobi M.; Nweke, Chinonye O. (International Journal Of Community Medicine And Public Health, 2017)
Background: Studies on definition of obesity using anthropometric measurements as indicators among children and adolescents are scanty in Nigeria. This study defined obesity among children and adolescents in south west Nigeria using selected anthropometric characteristics. Methods:Participants were between 5 to 19 years. They were randomly recruited, until 2114 completed the procedure. Participant’s age and sex were obtained. Height, weight, waist circumference, and hip circumference were measured using standard procedures. Data were analysed using descriptive and inferential statistics at p<0.05. Results: Average ages of males and females were 14.03±2.16years, and 9.57±2.17years respectively. There were significant differences in anthropometric measures according to gender and across age groups (p <0.05). Males were older, bigger, and taller than females. Females however had higher WHR and WtHR ratios. Waist circumference was significantly associated (p>0.05) with gender (χ2 = 23.762, p = 0.001) and age (χ2 = 25.585, p = 0.001), with a higher percentage of males in the obese group. The 25th and 95th percentile of anthropometric measures were: BMI (kg/m2) = ≤15.9, ≥23.0; WC = ≤56.0, ≥73.0cm; WHR = ≤0.82, ≥0.97 and WHtR ≤0.40, ≥0.48 for underweight and obese respectively. Conclusions:Prevalence of obesity was low; WC was the most sensitive indicator for obesity. Gender and age influenced anthropometric indices.